2016
DOI: 10.1371/journal.pone.0168562
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Effects of Rosiglitazone in Obesity-Impaired Wound Healing Depend on Adipocyte Differentiation

Abstract: Combined diabetes-obesity syndromes severely impair regeneration of acute skin wounds in mouse models. This study assessed the contribution of subcutaneous adipose tissue to exacerbated wound inflammatory conditions. Genetically obese (ob/ob) mice showed an increased expression of positive transcriptional effectors of adipocyte differentiation such as Krüppel-like factor (KLF)-5 and peroxisome proliferator-activated receptor (PPAR)-γ and an associated expression of leptin and fatty acid-binding protein (FABP)-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 73 publications
1
5
0
Order By: Relevance
“…This finding was consistent with the conclusion of Li et al [28]. Additionally, Siebert et al [29] demonstrated that rosiglitazone had anti-inflammatory effects through its effect on PPAR- γ protein in adipocytes. Similarly, our results indicated that obese mice which received rosiglitazone treatment had significantly decreased levels of ITGAM and NF- κ B protein expression associated with inflammatory response and had decreased levels of polarized M2 macrophages, which ultimately suppressed the production of proinflammatory cytokines TNF- α , IL-6, and IL-1 β and promoted the secretion of anti-inflammatory cytokine IL-10.…”
Section: Discussionsupporting
confidence: 92%
“…This finding was consistent with the conclusion of Li et al [28]. Additionally, Siebert et al [29] demonstrated that rosiglitazone had anti-inflammatory effects through its effect on PPAR- γ protein in adipocytes. Similarly, our results indicated that obese mice which received rosiglitazone treatment had significantly decreased levels of ITGAM and NF- κ B protein expression associated with inflammatory response and had decreased levels of polarized M2 macrophages, which ultimately suppressed the production of proinflammatory cytokines TNF- α , IL-6, and IL-1 β and promoted the secretion of anti-inflammatory cytokine IL-10.…”
Section: Discussionsupporting
confidence: 92%
“…In mice CXCL1 (KC) and CXCL2 (MIP-2), acting via CXCR2, regulate neutrophil chemotaxis and their levels are enhanced in obese individuals [ 45 , 46 ]. We evaluated the dependence of neutrophil infiltration into liver sinusoids on CXCR2 by pretreating obese and lean mice with its antagonist.…”
Section: Resultsmentioning
confidence: 99%
“…Chemokine C-X-C motif 10 (CXCL-10) was selected as a marker associated with inflammation in adipose tissue (Kochumon et al, 2020), as well as macrophage recruitment in other tissues (Petrovic-Djergovic et al, 2015). Finally, C-X-C motif ligand 2 (CXCL-2) was chosen as a pro-inflammatory chemokine that has been shown to be upregulated during adipogenic differentiation (Kusuyama et al, 2016;Siebert et al, 2016), and interleukin-6 (IL-6) was included as an additional pro-inflammatory adipokine that can modulate both lipid metabolism and macrophage polarization within adipose tissue (Trujillo et al, 2004;Braune et al, 2017). For this assay, three replicate scaffolds from each group (n = 3) were analyzed per ASC donor, and a total of five trials were performed with different ASC donors (N = 5).…”
Section: Quantitative Analysis Of the Effects Of Perfusion Bioreactormentioning
confidence: 99%